PENGEMBANGAN MEDIA PEMBELAJARAN SISWA BERBASIS GAME ANDROID PADA MATERI SISTEM KOMPUTER DI SMK MUHAMMADIYAH 1 PADANG - Dhika, Zulyasep Azdkiya; Mary, Thomson; Kurniawan, Haris (Universitas Muhammadiyah Tapanuli Selatan, 2025)
Based on the results of observations conducted by researchers, especially at SMK Muhammadiyah 1 Padang, it is known that the teaching methods used in science subjects at SMK Muhammadiyah 1 Padang still use lecture and discussion methods with teaching aids and conventional methods that have not been oriented towards the implementation of educational activities. The purpose of this study was to develop an educational Android game for 10th grade computer science students at SMK Muhammadiyah 1 Padang. To determine the level of validity of educational android games in the field of computer science at SMK Muhammadiyah 1 Padang. This type of research is research and development (RD). The results of educational games for learning through media training achieved an average media validation value of 84.58 which can be classified as